(3JMQjQ cJGH GdcQI GdeJMQcIs - (3GhWhdhbSs
(3ChdgG (B:s
(3GdfbW GdJi JJMQc MQcI eYJOdI gi GdJi JSjQ ai CReGf eJSGhjI ebGOjQ eJSGhjI eJTGHgI s
(3BNQgG (B:s
(3NQL ef eQcR GdcQI Edi eQcR OGFQI hPdc eG CQOfG Je cJGH GdcQI GdeJMQcI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1452s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs